2017
DOI: 10.48550/arxiv.1706.04648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Non-Perturbative Lattice Regularization of an Anomaly-Free $1 + 1d$ Chiral $SU(2)$ Gauge Theory

Michael DeMarco,
Xiao-Gang Wen

Abstract: We present a numerical treatment of a novel non-perturbative lattice regularization of a 1 + 1d SU (2) Chiral Gauge Theory. Our approach follows recent proposals that exploit the newly discovered connection between anomalies and topological (or entangled) states to show how to create a lattice regularization of any anomaly-free chiral gauge theory. In comparison to other methods, our regularization enjoys on-site fermions and gauge action, as well as a physically transparent fermion Hilbert space. We follow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Following the ideas in Ref. 52, we can also construct a strongly interacting metallic phase of spin-1/2 electrons where the left-movers and right-movers have very different behavior. We will call such metallic phases chiral metallic phases.…”
Section: Electronsmentioning
confidence: 99%
“…Following the ideas in Ref. 52, we can also construct a strongly interacting metallic phase of spin-1/2 electrons where the left-movers and right-movers have very different behavior. We will call such metallic phases chiral metallic phases.…”
Section: Electronsmentioning
confidence: 99%
“…Since the 2+1D domain wall fermion is nothing but 2+1D classical formulation of a 2D Topological Insulator [126][127][128] (Chern Insulator/IQHE without time-reversal symmetry; class A in 2D classified by Z), our result here provides the explicit procedure to bridge between the two constructions for 1+1D chiral gauge theories, the 2+1D classical construction of domain wall fermion with boundary interactions to decouple the mirrormodes [114] and the 2D quantum Hamiltonian construction of TI/TSC with gapped boundary phases [109][110][111][112][113]. And the mirror-fermion model in terms of overlap fermions is obtained precisely as the 1+1D low-energy effective local lattice theory, and it can describe directly the gapless/gapped boundary phases.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, this question of decoupling the mirror degrees of freedoms in the 345 model was also studied by Wang and Wen [110] from the point of view of the Hamiltonian construction based on Topological Insulators/Superconductors [109][110][111][112][113]: based on the effective bosonic (bosonized) description of the 2D Chern Insulator by the bulk Chern-Simon gauge theory and the boundary chiral-boson theory with sine-Goldon couplings, it was shown that the boundary phase can be fully gapped in the 345(0) model by the two sine-Goldon couplings required precisely to break the two "would-be anomalous" global U(1) symmetries in the mirror sector. This result suggests that the mirror fermions can be decoupled by the suitable choice of the coupling strengths of the symmetry-breaking interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In that setting, the goal is to find a way to gap the fermion doublers, leaving the original fermions unscathed, in the hope of finding a route to constructing chiral gauge theories on the lattice. This idea was first proposed by Eichten and Preskill [15] and interesting variants on the theme have been explored by a number of different authors over the years [16][17][18][19][20][21][22][23]. Nearly all of these approaches rely on strong coupling effects at the lattice scale, where irrelevant operators can drive the low energy dynamics.…”
Section: Introductionmentioning
confidence: 99%